Pengukuran Nilai Wajar Aset (IAS 13) dan Aset Tidak Berwujud (IAS 38) terhadap Manajemen Laba - Diyah Pujiati (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
This study aims to examine whether level 1 fair value assets and intangible assets have a significant impact on earnings management within Indonesia's banking service sector. The research sample included 136 foreign exchange banks that reported financial data on the Indonesia Stock Exchange between 2019 and 2022. Data analysis was conducted using multiple linear regression. The findings show a significant effect of level 1 fair value assets on earnings management in Indonesia's banking industry, while no significant effect was found for intangible assets. The study concludes that fair value asset measurements do not influence earnings management, whereas intangible assets do. To support ongoing improvements in financial accounting standards, it is recommended to implement the guidelines from accounting standards 68 (measuring fair value) and 19 (intangible assets), and to comply with the requirements of International Accounting Standards (IAS) 13 and IAS 38. Additionally, continuous enhancements to corporate governance and internal control systems are essential for boosting entity performance, improving financial reporting processes, and increasing earnings quality. This study serves as a preliminary investigation into the effect of intangible assets and level 1 fair value measurements on earnings management in the Indonesian banking sector.